Bronchoalveolar lavage single-cell transcriptomics reveals immune dysregulations driving COVID-19 severity - Clinton Njinju Asaba; Razieh Bitazar; Patrick Labonté; Terence Ndonyi Bukong (PLoS ONE, 2025)
The continuous threats posed by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), the virus that causes COVID-19, including the emergence of potentially more infectious and deadly variants, necessitate ongoing studies to uncover novel and detailed mechanisms driving disease severity. Using single-cell transcriptomics, we conducted a secondary data analysis of bronchoalveolar lavage fluid (BALF) from COVID-19 patients of varying severities and healthy controls to comprehensively examine immune responses. We observed significant immune cell alterations correlating with disease severity. In severe cases, macrophages showed upregulation of pro-inflammatory genes TNFα and IL1β, contributing to severe inflammation and tissue damage. Neutrophils exhibited increased activation, marked by S100A8, CXCL8, and IL1β expression, with extended viability and reduced phagocytosis. Genes such as MCL1 and HIF1α supported extended viability, while MSR1 and MRC1 indicated reduced phagocytosis. Enhanced formation of neutrophil extracellular traps (NETs) and reduced clearance, indicated by NET-associated markers, were linked to thrombo-inflammation and organ damage. Both macrophages and neutrophils in severe cases showed impaired efferocytosis, indicated by decreased expression of MSR1 and TREM2 in macrophages and downregulation of FCGR3B in neutrophils, leading to the accumulation of apoptotic cells and exacerbating inflammation. Severe cases were characterized by M1 macrophages with high TNFα and IL1β, while milder cases had M2 macrophages with elevated PPARγ. Dendritic cells (DCs) in severe cases exhibited reduced proportions and attenuated expression of MHC class I genes (HLA-A, HLA-B, HLA-C) and co-stimulatory molecules (CD80, CD86), alongside increased cytochrome c expression, indicating impaired antigen presentation and enhanced apoptosis. NK and T cells in severe cases demonstrated altered receptor and gene expression, with increased activation markers IFNγ and ISG15, suggesting a paradoxical state of activation and exhaustion. This analysis highlights the critical role of dysregulated neutrophil, macrophage, dendritic cell, NK, and T cell responses in severe COVID-19, identifying potential therapeutic targets and providing novel insights into the disease.